Application of the AES Cryptographic Algorithm for E-mail Encryption and Description - Atep Hidayat (Sean Institute, 2022)
The problem of sending email data or messages has become an important problem in the era of information technology as it is today. Sometimes this data must be confidential so that it is not publicly known. If the data is known, then the data can be misused for crimes by other people. Cryptography is one of the security tools used to hide a message. Cryptography is already used in all areas of security. For this reason, security is needed by encrypting and decrypting email data using cryptographic algorithms. One of the most popular cryptographic algorithms is the RSA algorithm. This research will discuss the implementation of the RSA cryptographic algorithm for email encryption and decryption. For testing, a java-based email client program was created with message encryption and message decryption features. This application uses the Java programming language and Netbeans 7.4 as an editor. The mail server used is Google Mail. The initial step of this research is to download email from Google servers and encrypt the message. The second step is to decrypt the message to verify if the message is still the same as the original message before encryption. The results of this study are applications that can encrypt and decrypt messages using the RSA cryptographic algorithm. With this application, it is hoped that mail delivery will be much safer. Because encrypted email will generate a random decimal number whose value is unknown.